A Radiological Study of Age Estimation from Epiphyseal Fusion of Distal End of Femur in the Central India Population - Tirpude, Bipinchandra; Patond, Swapnil; Murkey, Pankaj; Nagrale , Ninad (Journal of Indian Academy of Forensic Medicine, 2015)
There is no statistical data to establish variation in epiphyseal fusion in population in population of central India. This significant oversight can lead to exclusion of persons of interest in a forensic investigation. Epiphyseal fusion of the distal femur in 150 individuals was analyzed on radiological basis to assess the range of variation of epiphyseal fusion at each age. In the study the X-ray films of the subjects were divided into three groups on the basis of degree of fusion. Firstly, those which were showing No Epiphyseal Fusion (N), secondly those showing Partial Union (PC), and thirdly those showing Complete Fusion (C). Observations made were compared with the previous radiological studies.The ossification at distal end of femur at the Knee joint in Males and Females is completed in all instances (100%) at the age groups of 18-20 years and 16-20 year respectively.From this study, range of 1-2 years of margin of error can be concluded.